1987
DOI: 10.1017/s0022143000005396
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Basal Sliding and Deformation of Basal Drift at Sub-Freezing Temperatures

Abstract: In a tunnel at the base of sub-polar Urumqi Glacier No. 1, China, three new mechanisms of glacier flow at sub-freezing temperatures have been observed.Taken individually or in combination, these modes of flow can account for nearly all (60-80%) of the overall glacier motion and, yet, they act only within the lowermost 1-2% of the effective glacier thickness. These mechanisms are:(I) enhanced deformation of the frozen and ice-laden subglacial drift; (2) motion across discrete shear planes or shear bands within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
155
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(165 citation statements)
references
References 50 publications
10
155
0
Order By: Relevance
“…In conclusion, it appears that the large mean shear strain rate of the debris-laden ice in situ found by Echelmeyer and Wang (1987) must be explained by discontinuous slip as mentioned in section 5.…”
Section: Creep Ex Perimen T S On D Ebris-lad En Icementioning
confidence: 59%
See 3 more Smart Citations
“…In conclusion, it appears that the large mean shear strain rate of the debris-laden ice in situ found by Echelmeyer and Wang (1987) must be explained by discontinuous slip as mentioned in section 5.…”
Section: Creep Ex Perimen T S On D Ebris-lad En Icementioning
confidence: 59%
“…This speed was approximately 60% of the surface speed, showing that a large part of the glacier movement at this point was due to deformation of the iceladen till bed, which was ~ 0. this layer was less than 2% of the total thickness of the glacier. Echelmeyer and Wang (1987) treated the till as a thin boundary layer and compared the mean rate of shear strain across its 0.35 m thickness with that of the adjacent layer of ice. They assumed that the shear stress was approximately the same in the basal ice and the till, and thereby concluded that the mean effective viscosity for the ice is more than 100 times that of till.…”
Section: Bed Deformationmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research on the mechanical behaviour of basal debris-laden ice has produced a range of results. In general, observations of the behaviour of naturally occurring debrisladen ice suggest that near the melting point, the presence of sediment softens the ice, probably as a result of a liquid water effect (Duval 1977;Echelmeyer & Wang 1987;Cohen 2000). However, there is some evidence that at colder temperatures, debris-laden ice is stronger than clean ice (Lawson 1996).…”
Section: Problem Rationale and Approachmentioning
confidence: 99%